2006
DOI: 10.1128/jcm.02236-05
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Nontypeable Group B Streptococcus

Abstract: Traditionally, the capsular polysaccharide (CPS) antigen has been used to distinguish between the nine known serotypes of group B streptococcus (GBS) by classical antibody-antigen reactions. In this study, we used PCR for all CPSs and selected protein antigens, multilocus sequencing typing (MLST), and pulsed-field gel electrophoresis (PFGE) to molecularly characterize 92 clinical isolates identified as nontypeable (NT) by CPS-specific antibody-antigen reactivity. The PCR and MLST were performed on blinded, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 39 publications
(51 reference statements)
4
43
0
1
Order By: Relevance
“…Representatives of this group displayed ST1, and the only serotype IV isolate exhibited ST196, a DLV of ST1. NT isolates closely related to type V isolates, as determined by PFGE, have been described previously (1), and NT isolates ultimately classified as ST1 in the present study have been previously reported to carry the capsular polysaccharide synthesis-specific gene characteristic of serotype V (35). Indeed, isolates of serotypes IV and V have been previously described as belonging to CC1 (29).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Representatives of this group displayed ST1, and the only serotype IV isolate exhibited ST196, a DLV of ST1. NT isolates closely related to type V isolates, as determined by PFGE, have been described previously (1), and NT isolates ultimately classified as ST1 in the present study have been previously reported to carry the capsular polysaccharide synthesis-specific gene characteristic of serotype V (35). Indeed, isolates of serotypes IV and V have been previously described as belonging to CC1 (29).…”
Section: Discussionmentioning
confidence: 79%
“…DNA was extracted as previously described (13) and digested with 40 U of SmaI. PFGE results were interpreted according to the criteria previously reported (35). Isolates with indistinguishable PFGE patterns were assigned to identical PFGE subtypes.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this method could be a useful adjunct for vaccine development and surveillance, as it identifies GBS strains that are serologically nontypeable. Nontypeable strains often have CPS genes but are low-level producers or may have modified capsular structures that do not react to antisera from any of the 10 known serotypes (25). Another serotyping method, used by 2 of 14 participating centers, included immunodiffusion with in-house antisera.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract serves as the natural reservoir for GBS and is expected to be the source of vaginal colonization 23,43 . Pregnant women who are colonized with GBS might develop infections of the urinary tract, bacteremia, chorioamnionitis, and postpartum endometritis 23,47,48 , thus increasing the risk of PTD, PPROM and perinatal transmission [49][50][51] , resulting in neonatal sepsis and meningitis 45,52,53 . A prevalence of 7 -25% GBS colonization in AV has been reported in women between 35 and 37 weeks of gestation 54 , with intrauterine infection associated with the ability of GBS to ascend from the lower genital tract and colonize the upper genital tract [54][55][56] .…”
Section: Group B Streptococci (Gbs)mentioning
confidence: 99%